Conservation confidential : a wild path to a less polarizing and more effective activism - Friedman, Mitch (Latah Books, 2025)
Conservation Confidential recounts the wild path Mitch Friedman took from radical Earth First! activist engaging in controversial protests to the founder and longtime director of Conservation Northwest. The book documents challenges, success stories, and key lessons along the way to helping preserve Northwest ancient forests, peaceably recover wolves in the region, and much more. Part memoir, part guide on strategy for activists and liberal citizens, Conservation Confidential offers the distilled wisdom of experience that Friedman searched for as a young activist but couldn't find. These provocative lessons are timely not only for conservation campaigns but for our national political moment at large, extolling the virtues of collaborative tactics that succeed by enacting common values rather than polarizing. Here is the rare instance of an accomplished activist leader challenging his own movement to reject its hubris to better serve both nature and our ailing democracy.